2019
DOI: 10.1021/acsanm.9b01407
|View full text |Cite
|
Sign up to set email alerts
|

Migration and Growth of Silver Nanoparticles in Zeolite Socony Mobil 5 (ZSM-5) Observed by Environmental Electron Microscopy: Implications for Heterogeneous Catalysis

Abstract: Silver metal nanoparticles are among the most widely studied nanoparticles. They are widely used heterogeneous catalysts used for many purposes such as antisepsis, hydrogenation, and carboxylation but also for the trapping of xenon in nuclear test and detection facilities. The catalytic activity and adsorption capacity of silver nanoparticles, which depend on their size distribution and dispersion on the support, generally decrease with time because of agglomeration of the metal into larger particles. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
(72 reference statements)
2
9
0
Order By: Relevance
“…During MeOH photooxidation, Ag NP sintering with ∼6 nm of diameter can be observed after 1 h of reaction (Figure c) and becomes more pronounced after 12 h of reaction (Ag NP diameters of >20 nm; Figure d). The same phenomenon was observed by Monpezat et al on Ag-supported ZSM-5 upon thermal treatment from RT to 350 °C under nitrogen. The detailed sintering mechanism responsible for the growth of Ag NPs and the quantification of Ag species that diffuse from the core to the surface of the zeolite crystals upon thermal treatment were studied by environmental high-angle annular dark-field scanning transmission electron microscopy combined with fast electron tomography.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…During MeOH photooxidation, Ag NP sintering with ∼6 nm of diameter can be observed after 1 h of reaction (Figure c) and becomes more pronounced after 12 h of reaction (Ag NP diameters of >20 nm; Figure d). The same phenomenon was observed by Monpezat et al on Ag-supported ZSM-5 upon thermal treatment from RT to 350 °C under nitrogen. The detailed sintering mechanism responsible for the growth of Ag NPs and the quantification of Ag species that diffuse from the core to the surface of the zeolite crystals upon thermal treatment were studied by environmental high-angle annular dark-field scanning transmission electron microscopy combined with fast electron tomography.…”
Section: Resultssupporting
confidence: 86%
“…12 However, zeolite-supported clusters frequently suffer from sintering under thermal reaction conditions, which is manifested by the migration and agglomeration of metallic species on the external surface of the zeolite. Recently, Monpezat et al 13 quantified the sintering process and found that the micropores can only prevent the migration and coalescence of Ag particles with diameters of >0.5 nm. Moreover, a large fraction of Ag NPs (more than 85%) are subjected to sintering at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in experimental and theoretical techniques have provided insights into the sintering mechanism at the atomic level. , Sintering can occur via two pathways. One is based on the migration and coalescence of metal NPs driven by the decrease in surface energy, and the other is the atomic (Ostwald) ripening, in which mobile atomic species detach from one NP, diffuse over the support surface (or gas phase), and finally attach to another NP, resulting in the growth of large particles and disappearance of small particles owing to the difference in the stability of surface atoms. Recent microscopic and DFT studies have shown that Ostwald ripening is the dominant process in the growth of metal NPs. When the binding strength between the mobile adatom and support is higher than the cohesive energy of the metal NPs, the mobile adatom liberated from the metal NPs is trapped by the anchoring site of the support, leading to redispersion of the metal NPs to SACs.…”
Section: Introductionmentioning
confidence: 99%
“…Some particles are large due to more dispersion of nanoparticles on zeolite and some particles are small due to less dispersion. Dispersion of the particles on zeolite varies with the synthetic conditions (Monpezat et al, 2019). The aggregation of high-energy surface particles causes large size.…”
Section: Characterizationmentioning
confidence: 99%